2018
DOI: 10.1071/rd17432
|View full text |Cite
|
Sign up to set email alerts
|

CASA-Mot in mammals: an update

Abstract: Sperm motility is one of the most widely used parameters of sperm quality. Computer-aided sperm motility analysis (CASA-Mot) systems were developed to reduce the subjectivity of sperm motility assessment, and have had broad scientific and practical acceptance. In this review, the sources of variation and current applications of this technology and its relationships with other sperm quality tests are described in detail. Despite remarkable advances in the technique, there is still great need for standardisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 160 publications
1
47
0
5
Order By: Relevance
“…We have demonstrated that such analysis, performed here automatically on large sample sizes totalling hundreds of swimmers, and incorporating information from 90% of the length of the flagellum, is realisable with readily-available imaging and computational techniques, and thus represents a viable framework for a new generation of detailed flagellar CASA, and more generally the advent of computer-assisted beat-pattern analysis (CABA). The introduction of traditional CASA has had a substantial impact in theriogenology, for example enabling systematic quality control and assurance in the livestock breeding industry [9], as well as fundamental cell science, with extensive fundamental studies of sperm function [11][12][13]. Further, the expansion into near-complete planar flagellar waveform capture offers the prospect of novel directions for the exploration of male gamete motility, and flagellated or ciliated organisms more generally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that such analysis, performed here automatically on large sample sizes totalling hundreds of swimmers, and incorporating information from 90% of the length of the flagellum, is realisable with readily-available imaging and computational techniques, and thus represents a viable framework for a new generation of detailed flagellar CASA, and more generally the advent of computer-assisted beat-pattern analysis (CABA). The introduction of traditional CASA has had a substantial impact in theriogenology, for example enabling systematic quality control and assurance in the livestock breeding industry [9], as well as fundamental cell science, with extensive fundamental studies of sperm function [11][12][13]. Further, the expansion into near-complete planar flagellar waveform capture offers the prospect of novel directions for the exploration of male gamete motility, and flagellated or ciliated organisms more generally.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extensive user intervention still required for such packages as well as basic thresholding based techniques, for example by Smith et al [4] who reported on the beats of 36 swimmers, has to date largely restricted population-level computer-assisted sperm analysis (CASA) to head-based investigations [5][6][7][8] and assessments of flagellar morphology [9], with flagellar waveforms neglected. Despite such limitations, and its only partial acceptance in clinical diagnostics [10], CASA has also found extensive application in reproductive toxicology, quality assurance for semen marketing in livestock breeding, improvements in sperm technologies such as cryopreservation, and studies of basic sperm function [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers must be aware of some caveats, some of which have been explained in more depth in other articles in this special volume (Bompart et al 2018;Yániz et al 2018aYániz et al , 2018b AQ1 ; Yeste et al 2018). Adequate equipment and standardised protocols for sample preparation and image acquisition are compulsory, but details are frequently overlooked (e.g.…”
Section: Going Beyond the Casa Systemsmentioning
confidence: 99%
“…Then, the sperm sequences are automatically analysed by the computer in a concise time [11]. Moreover, CASA-Mot systems provide a battery of kinematic quantitative parameters that define the sperm cell motility rather than the progressivity [12].…”
Section: Introductionmentioning
confidence: 99%